Applied Reconfigurable Computing: 11th International Symposium, ARC 2015, Bochum, Germany, April 13-17, 2015, Proceedings - Sano, Kentaro; Soudris, Dimitrios; Hübner, Michael; Diniz, Pedro C (Lecture Notes in Computer Science, 2015)
This book constitutes the refereed proceedings of the 11th International Symposium on Applied Reconfigurable Computing, ARC 2015, held in Bochum, Germany, in April 2015. The 23 full papers and 20 short papers presented in this volume were carefully reviewed and selected from 85 submissions. They are organized in topical headings named: architecture and modeling; tools and compilers; systems and applications; network-on-a-chip; cryptography applications; extended abstracts of posters. In addition, the book contains invited papers on funded R&D - running and completed projects and Horizon 2020 funded projects.